DESIGN AND RESEARCH ARM OF THE CONVERTER SLIDE - ZHAO LiJuan; ZHOU WenChao; TIAN Zhen; MENG Yang (Jixie qiangdu)
A hydraulic mechanical arm is designed,which realizes the installation and disassembly of the converter and the mechanical and automation of the transport. In order to verify the rationality of the design,through the Pro/Engineer,ADAMS,ANSYS structural co-simulation platform,a key part of the mounting arm coupled to the flexible member is rigid virtual prototype model. According to the practical application of the mechanical arm,telescopic hydraulic cylinders to determine the scope,and its validation,ensuring that meet the requirements. By ADAMS kinematics and dynamics simulation analysis,mounting arm motion displacement curve and the mounting process load lifting arm high dynamic stress areas. Based on ANSYS software provides mounting arm modal constraints analysis,identify the natural frequency and vibration mode of mounting arm,optimize its structural strength and resistance to impact and improve the ability of vibration reference.